2014
DOI: 10.1097/mjt.0b013e318269175f
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Placebo-Controlled Trial of Selenium Supplementation in Patients With Type 2 Diabetes

Abstract: Selenium is an antioxidant trace element. Patients with diabetes are shown to have increased oxidative stress together with decreased selenium concentrations. Whether raising serum selenium will improve blood glucose management in diabetes is largely unknown. In this randomized, double-blind placebo-controlled trial, we assessed the effects of selenium on blood glucose, lipid profile, and oxidative stress in 60 patients with type 2 diabetes. Selenium 200 µg/d or placebo was administered orally for 3 months. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(83 citation statements)
references
References 31 publications
1
77
1
4
Order By: Relevance
“…A recent cross-sectional study showed that even Se intake levels considered as adequate were associated with higher T2D prevalence compared to sub-optimal Se intake in a Chinese population (Wei et al, 2015). Likewise, a trial conducted with T2D patients reported worsened hyperglycemia in those subjects who had received Se in form of daily doses of 200 μg sodium selenite for 3 months compared to the placebo group (Faghihi et al, 2014). Interferences of Se and selenoproteins with the insulin-regulated carbohydrate and lipid metabolism are discussed in detail in a recent review (Steinbrenner, 2013), wherein GPx-1 and SeP are highlighted as mediators of adverse effects of Se regarding insulin sensitivity.…”
Section: Adverse Effects Of Antioxidants In Human Studiesmentioning
confidence: 99%
“…A recent cross-sectional study showed that even Se intake levels considered as adequate were associated with higher T2D prevalence compared to sub-optimal Se intake in a Chinese population (Wei et al, 2015). Likewise, a trial conducted with T2D patients reported worsened hyperglycemia in those subjects who had received Se in form of daily doses of 200 μg sodium selenite for 3 months compared to the placebo group (Faghihi et al, 2014). Interferences of Se and selenoproteins with the insulin-regulated carbohydrate and lipid metabolism are discussed in detail in a recent review (Steinbrenner, 2013), wherein GPx-1 and SeP are highlighted as mediators of adverse effects of Se regarding insulin sensitivity.…”
Section: Adverse Effects Of Antioxidants In Human Studiesmentioning
confidence: 99%
“…The outcome was the TBARS concentration, which has also been recently used as an endpoint in clinical trials of selenium supplementation in patients with Type 2 diabetes [36], of exercise training in hemodialysis patients [37]. The association between catechins and biomarkers of oxidation measured with TBARS has been the focus of interest of many studies, particularly because of the abundance of catechins in the human diet.…”
Section: Discussionmentioning
confidence: 99%
“…Дослідженням впливу короткострокового психологічного стресу на концентрацію ліпідів у крові людей присвячено немало робіт [2,3], а про передзабійний стрес у тварин у літературі є дуже мало відомостей. Стресовий стан у сільського-сподарських тварин і свиней, зокрема, викликає не тільки економічні втрати, але й погіршення якості продукції [4][5][6].…”
Section: літературний оглядunclassified
“…Досі залишається невивченою зона ризику набутих хвороб печінки (гепатит, фіброз, цироз) у людей, які мають схильність до раку молочної залози (є фактом, що рак викливається вірусом). Залишається невивченим питання, щодо ймовірності не тільки набути хвороби печінки, а й можливості розвитку раку печінки -гепатоцерулярної карциноми [2]. Захворювання печінки зазвичай має тривалий перебіг, без клінічних симтомів.…”
Section: вступunclassified